A systematic review on the health of African immigrants in the United States: synthesizing recommendations for future research. Issue 2 (30th March 2020) - Semprini, Jason
Abstract : Purpose: The purpose of this paper is to conduct a systematic review of published literature studying the health of African immigrants in the USA and to develop a formal set of recommendations for future researchers aiming to improve the health outcomes in this population. Design/methodology/approach: A comprehensive search was initiated on PubMed, Cochrane, ERIC, DOAJ, Prospero and Scopus databases. Final inclusion criteria were: systematic reviews, studying African Immigrants in the USA, measuring a clinical health outcome, since 1999. Articles were screened in four stages by title, abstract, full-text of the review and full-text of the primary studies within each review. Data was abstracted by identifying general information, study population, outcome measurements, conclusions and recommendations of each review. Findings: In the initial search, 519 potential reviews were identified. After removing duplicates, 473 articles were excluded by screening the title or abstract. After a full-text review of each article and primary study within each article, nine reviews were included in the final synthesis. Reviews covered Female Genital Cutting and Pregnancy Outcomes, Caesarean Births, Gestational Diabetes, Cancer, HIV/AIDS, Body-weight and Acculturation. Among the primary reports included in the final synthesis, less than 50 per cent studied African immigrants in the USA. African Americans living in the USA made up only 11 per cent of the pooled study sample. Research limitations/implications: Immigrants from Africa are one of the fastest-growing populations in the USA. This group has been underrepresented in health research, leading to a poor understanding of the group's health outcomes. Health researchers must adopt recommendations and prioritize studies that meet the health needs of Africans during this time of demographic transition. Originality/value: Systematic reviews represent a bedrock of medical evidence and signify a solid understanding of accepted knowledge in the field. Systematic reviews, however, do not necessarily constitute the end of discovery. Researchers can use existing systematic reviews to critique previous studies or initiate future research. There remain significant research gaps analyzing the health outcomes, behaviors and treatment of subgroups of African immigrants living in the USA. Future research should shift toward the growing needs of the population, leveraging the strengths and diversity of African immigrants now living in the USA.